Kiss him, not me! 13 - Junko (Mangaka) (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
"I can hardly believe that Mutsumi-senpai and I are a couple. And on top of that, Mirage Saga has a sequel? Pinch me, I must be dreaming. But maybe I'm not in paradise after all. I got carried away with the Mirage Saga event and ended up ditching my date with Mutsumi-senpai to spend time with his friend Yashiro. And when Mutsumi-senpai finds out about everything, he forces me to face an unthinkable question: who do I love more, Shion or Mutsumi-senpai? Ohhh--what will I do? Do I go with Boys Love or the boy I love?"--Back cover.